Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41467-023-40372-0
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and host environments determine community ecology and keystone species in a synthetic gut bacterial community

Abstract: A challenging task to understand health and disease-related microbiome signatures is to move beyond descriptive community-level profiling towards disentangling microbial interaction networks. Using a synthetic gut bacterial community, we aimed to study the role of individual members in community assembly, identify putative keystone species and test their influence across different environments. Single-species dropout experiments reveal that bacterial strain relationships strongly vary not only in different reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 72 publications
5
3
0
Order By: Relevance
“…The stabilisation in four transfers we observed under defined media is consistent with those observed in complex, undefined growth media 79,23 . However, stabilisation in taxonomic composition may not reflect functional stabilisation since composition does not capture potential shifts in metabolic activities of species and community.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The stabilisation in four transfers we observed under defined media is consistent with those observed in complex, undefined growth media 79,23 . However, stabilisation in taxonomic composition may not reflect functional stabilisation since composition does not capture potential shifts in metabolic activities of species and community.…”
Section: Resultssupporting
confidence: 87%
“…While discerning between these two sources is difficult in in vivo settings where available nutrients reaching the community are hard to track, in vitro synthetic communities provide a tractable approach to delineate the contribution of the biotic supply. Previous work has shown that synthetic gut bacterial communities can be readily assembled through serial dilution and remain stable over multiple transfers 79 . However, these communities were assembled in undefined growth media obscuring the relation between specific nutrient components and community composition.…”
Section: Figurementioning
confidence: 99%
“…Most taxa from the the cirrhotic guild were either not present in the “healthy individuals”-network (as they didn’t pass the prevalence threshold in the healthy individuals dataset) or had much fewer interactions and were not included in a guild. Overall, this suggests that the interactions identified between the cirrhotic species are context-dependent, a finding that has already been documented in other contexts Weiss et al [2023] and K. Faust [2021].…”
Section: Application To Liver Cirrhosissupporting
confidence: 74%
“…Meeting the nutritional and environmental needs of microorganisms requires thoughtful selection of medium components such as carbohydrates, nitrogen compounds, vitamins, and minerals [ 29 , 30 ]. For example, carbohydrates act as energy sources, while nitrogen compounds are fundamental for protein metabolism.…”
Section: Strategic Cultivation Medium Composition For Gut Microbial R...mentioning
confidence: 99%